miR-142 deficit in T cells during blast crisis promotes chronic myeloid leukemia immune escape - Fang Chen; Dandan Zhao; Yongfang Xu; Yi Zhang; Min-Hsuan Chen; Khyatiben V. Pathak; Nate Hansen; Brooke Lovell; Yong Liang; Katrina Estrella; Wei-Le Wang; Lucy Ghoda; et al. (Nature Communications)
Abstract We reported that an acquired miR-142 deficit transforms chronic phase (CP) chronic myeloid leukemia (CML) leukemic stem cells (LSCs) into blast crisis (BC) LSCs. Given the role of miR-142 in the development and activity of the immune system, we postulated that this deficit also promotes LSC immune escape. Herein, we report on IL-6-driven miR-142 deficit occurring in T cells during BC transformation. In CML murine models, miR-142 deficit impairs thymic differentiation of lymphoid-primed multipotent progenitors (LMPP) into T cells and prevents T cells’ metabolic reprogramming, thereby leading to loss of T cells and leukemia immune escape. Correcting miR-142 deficit with a miR-142 mimic compound (M-miR-142), alone or in combination with immune checkpoint antibodies, restores T cell number and immune activity, leading to LSC elimination and prolonged survival of BC CML murine and patient-derived xenograft models. These observations may open new therapeutic opportunities for BC CML and other myeloid malignancies.